A bidirectional diode containing multilevel inverter topology with reduced switch count and driver. (30th June 2020) - Hosseinpour, Majid; Seifi, Ali; Rahimian, Mohmad Mohsen
Summary: In this paper, a bidirectional diode containing multilevel inverter is introduced to reduce the number of switching elements especially in the case of a high number of output voltage levels. In comparison with classic and recently introduced symmetrical topologies, which are trying to reduce the switch count, this topology has a lower number of semiconductor switches in the same number of output voltage levels. This makes the proposed inverter to be a suitable choice for medium voltage applications like renewable energy applications as well as medium voltage electric drives. Moreover, it can be used in a cascaded configuration for high voltage levels. To depict the performance of the proposed structure, a comprehensive comparison is made between this topology and classic and recently proposed symmetric topologies in terms of switch and gate driver count, power losses, and cost. The performance of the proposed symmetrical 11‐level converter is analyzed and simulated in MATLAB/Simulink for both PWM and selective harmonic elimination switching methods. Not only the results are desirable but also the experimental results of laboratory prototype validate the simulation results. Abstract : In this paper, a new bidirectional symmetric multilevel inverter is introduced to reduce the number of switches and drivers. Despite substituting switch by diode in its structure, it is capable to produce the desired output voltage without any voltage spike. The proposed multilevel inverter has significantly fewer switches than the existing structure, which reduces the volume and complexity of control and switching. The multilevel inverter configuration and operation principle are given in detail, and its design methods are described.